Democratic Perception and Attitudes of the Pre-Service Music Teachers in Turkey - Hatice Onuray Eğilmez; Özgür Eğilmez; Doruk Engür (International Journal of Evaluation and Research in Education (IJERE), 2018)
Democracy, a lifestyle as much as it is a form of government, begins to be learned in the family. The youth observe and acquire the democratic attitudes of their parents. The task of passing it on to the new generations and helping them acquire democratic values is the mission of schools, namely teachers. It is a commonly known fact that developmental level of countries shows parallelism with the democratic attitudes of individuals. It is important to understand the democratic perceptions and attitudes of teachers who are responsible for positioning democratic structure and thus raising the democratic level of countries. For this reason, the research aims to examine the democratic perceptions and attitudes of music teacher candidates in terms of some variables. Data collected using the democratic attitude scale were analyzed using t-test, Kruskal-Wallis H test, and Spearman’s correlation coefficient. Results showed that attitude scores did not change according to gender, level of parents’ education or the year students were in. Scale scores were negatively correlated with the amount of parents’ income. There was no correlation between the students’ GPAs and the scale scores. Music teaching requires a democratic environment intrinsically; therefore, the democratic perceptions and attitudes of the music teacher candidates who will carry out the music lessons in which they should maintain the democratic environment must be determined. As aforementioned notions suggest, this study is of the essence since the results will shed light on the academic staff in the institutions that train music teachers.